NILAI PENDIDIKAN KARAKTER DALAM NOVEL NEGERI 5 MENARA KARYA A FUADI (KAJIAN SOSIOLOGI SASTRA) - Asrorul Huda (EDU-KATA, 2021)
The purpose of this research is to express the value of character education contained in the novel Negeri Lima Menara works A. Fuadi published by PT Gramedia Pustaka mold 2011. While data collection techniques used are descriptive-interpretative and categorization techniques. In this case, the instrument used is the researcher himself. This means that researchers do the reading and analyzing the source data repeatedly until found the certainty and confidence. The next step is consulted with the tutors. The result of the research shows that in novel Negeri 5 Menara contains five dimensions of character education value that is, divine character education, moral character education, social character education, character education culture and aesthetic character education. The elements used in the novel Negeri 5 Menara as a conveyor of the value of character education that there are four things: 1) the theme, which became the main idea of ​​the storyline, 2) the background, which underlies the description as explanation story, 3) The story in the novel is so interesting, and 4) the style of language, based on the directness of meaning, which is used in this research is a rhetorical and figurative style.